2016
DOI: 10.1016/j.hjc.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

An effect of left ventricular hypertrophy on mild-to-moderate left ventricular diastolic dysfunction

Abstract: In mild-to-moderate LVDD patients, both FP and the Tei index were significantly higher when LVH was present. This may suggest LVH as a possible predictor for the future development of severe LVDD and diastolic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
10
1
1
Order By: Relevance
“…In hypertensive patients, left ventricular workload is increased, resulting in LVH, impaired left ventricular relaxation, left atrial enlargement, and increased risk of arrhythmia (especially atrial fibrillation) and HF . Previous studies have shown a relationship between the severity of LVH and LV geometry with diastolic dysfunction . In the present study, although left ventricular mass index was higher in the increased LVEDP group, there was no statistically significant difference between the two groups.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In hypertensive patients, left ventricular workload is increased, resulting in LVH, impaired left ventricular relaxation, left atrial enlargement, and increased risk of arrhythmia (especially atrial fibrillation) and HF . Previous studies have shown a relationship between the severity of LVH and LV geometry with diastolic dysfunction . In the present study, although left ventricular mass index was higher in the increased LVEDP group, there was no statistically significant difference between the two groups.…”
Section: Discussioncontrasting
confidence: 62%
“…However, ECG has a limited role in determining volume/pressure overload of the cardiac chambers. Although no specific ECG findings demonstrate the presence of diastolic dysfunction, there is evidence that certain ECG findings, such as electrocardiographic left ventricular hypertrophy (LVH) voltage criteria, P wave duration (PWD), P wave dispersion (PW DISP ), and P wave terminal force (PWTF) in the lead V I , are associated with LVDD …”
Section: Introductionmentioning
confidence: 99%
“…Echocardiographic LVH, which has been found and determined by LVMI, has a high potential for the possible occurrence of cardiovascular and cerebrovascular events, independent of the other well‐known risk factors . LVH is the most common pathological condition that induces LV diastolic dysfunction and is associated with unfavorable CV prognosis . As far as hypertensive patients are concerned, one should not forget concentric remodeling of the LV, which is not LVH, according to LVMI.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] LVH is the most common pathological condition that induces LV diastolic dysfunction and is associated with unfavorable CV prognosis. 33,34 As far as hypertensive patients are concerned, one should not forget concentric remodeling of the LV, which is not LVH, according to LVMI. For instance, a recent study of a general population has shown that older individuals with concentrically remodeled and eccentric hypertrophy show a higher rate of mortality and CV morbidity as compared with the rest of the population.…”
Section: Discussionmentioning
confidence: 99%
“…4 In this article, the authors, motivated by the high prevalence and morbidity of heart failure with preservation of ejection fraction 5 and the limited understanding of its pathophysiological background, 6 studied the impact of left ventricle hypertrophy in the progression of mild to moderate left ventricle diastolic dysfunction. Based on simple echocardiographic techniques and not on advanced modalities, which have not been completely implemented in clinical practice, 7 these researchers documented the strong relationship of left ventricle hypertrophy with a worsened global and diastolic left ventricle function, which is a finding with potential etiological implications.…”
mentioning
confidence: 99%